Financial Appraisal of MTN Sponsored Activities - the case of the Africa Cup of Nations, 2008. - Sopiimeh, Guido (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Business Administration